Human locomotion on snow: determinants of economy and speed of skiing across the ages. - Formenti, F; Ardigò, L; Minetti, A (Royal Society, 2005)
We explore here the evolution of skiing locomotion in the last few thousand years by investigating how humans adapted to move effectively in lands where a cover of snow, for several months every year, prevented them from travelling as on dry ground. Following historical research, we identified the sets of skis corresponding to the 'milestones' of skiing evolution in terms of ingenuity and technology, built replicas of them and measured the metabolic energy associated to their use in a climate-controlled ski tunnel. Six sets of skis were tested, covering a span from 542 AD to date. Our results show that: (i) the history of skiing is associated with a progressive decrease in the metabolic cost of transport, (ii) it is possible today to travel at twice the speed of ancient times using the same amount of metabolic power and (iii) the cost of transport is speed-independent for each ski model, as during running. By combining this finding with the relationship between time of exhaustion and the sustainable fraction of metabolic power, a prediction of the maximum skiing speed according to the distance travelled is provided for all past epochs, including two legendary historical journeys (1206 and 1520 AD) on snow. Our research shows that the performances in races originating from them (Birkebeiner and Vasaloppet) and those of other modern competitions (skating versus classical techniques) are well predicted by the evolution of skiing economy. Mechanical determinants of the measured progression in economy are also discussed in the paper.